Exploring Senior Citizens’ Health Insurance in India - Kumar Roy, Joydeep (Digital Repository of Theses - SSBM Geneva, 2025)
The financial preparedness of elderly Indians for healthcare expenses remains a critical concern, given the rising medical costs and limited accessibility to comprehensive insurance coverage. This study examines the current state of health insurance and alternative financing options for senior citizens in India, drawing insights from industry experts. The findings highlight significant gaps in financial measures, the need for innovative products, and the role of self-help attitudes in managing healthcare expenses. Open Market Consumer Survey responses indicate widespread concern over the inadequacy of existing financial instruments. Experts overwhelmingly support the need for new insurance models and financing mechanisms, as reflected in a high relevance outcome for innovative solutions. Additionally, the study underscores the importance of a proactive self-help approach, with experts rating it very high on a scale of significance in reducing financial burdens. The study further reveals that elderly Indians face difficulties in anticipating healthcare costs and exhibit moderate willingness to pay for adequate insurance coverage. However, there is strong consensus on the necessity for expanded healthcare financing options to bridge the gap between coverage and actual medical expenses. The Mini Imen Delphi methodology adopted to ascertain the current situation and forecast the future with interventions and policy level actions drew the wisdom from several industry experts with quantitative and qualitative responses. The findings suggest an urgent need for policy interventions, customized insurance products, and diversified healthcare financing options to make medical services more accessible and affordable for the elderly. Subsidized health schemes, micro-insurance models, pension-linked medical funds, and tax benefits for senior citizens could help mitigate financial distress. Additionally, promoting preventive healthcare measures and early financial planning can enhance financial security for aging individuals. This study calls for collaborative efforts between government agencies, private insurers, and financial institutions to develop comprehensive, elderly-friendly financial solutions. Without immediate intervention, India’s aging population will continue to face severe healthcare affordability challenges, emphasizing the need for structural reforms in healthcare financing.